Bahan Koleksi Anak yang Ada di Perpustakaan Kota Medan - Yusniah Yusniah; Rizki Febri Yanti; Dea Amanda; Suci Wahyu Tami Br Rambe; Sri Ramadhani; Putri Asa Parent (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This article discusses the provision of a collection of library materials for children at the Medan City Library. This article describes the description of planning activities and the method of procuring a collection of children's library materials at the Medan City Library. This research was carried out using a qualitative method with unstructured interviews. The conclusion of this mini research is to work on materials for children's collections that are not yet owned by the Medan City Library and add materials that are already owned by the Medan City Library in relatively small quantities, while the planning steps taken are Inventory of library materials, Analysis the need for children's library materials, determine preotitas. In addition, several methods of procuring library materials are carried out in the following ways: buyers, gifts, exchanges, donations, collaboration, endowments and self-publishing. Keywords: collection of library materials, procurement, planning, Medan city library